The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/tbed.13434
|View full text |Cite
|
Sign up to set email alerts
|

Co‐circulation and characterization of HPAI‐H5N1 and LPAI‐H9N2 recovered from a duck farm, Yogyakarta, Indonesia

Abstract: In July 2016, an avian influenza outbreak in duck farms in Yogyakarta province was reported to Disease Investigation Center (DIC), Wates, Indonesia, with approximately 1,000 ducks died or culled. In this study, two avian influenza (AI) virus subtypes, A/duck/Bantul/04161291‐OR/2016 (H5N1) and A/duck/Bantul/04161291‐OP/2016 (H9N2) isolated from ducks in the same farm during an AI outbreak in Bantul district, Yogyakarta province, were sequenced and characterized. Our results showed that H5N1 virus was closely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, only 4 (4.8%) of these intraregional papers can be categorised as purely South–South collaborations, with no involvement of co‐authors from UN agencies or research organisations associated with high‐income countries. This small subset of papers includes two papers focused on disease epidemiology in Indonesia including authors from Thailand and Indonesia (Eyanoer et al, 2011; Lestari et al, 2019), one paper on disease epidemiology in Myanmar involving authors from Myanmar and Thailand (Mon et al, 2012), and one paper on the efficacy of animal vaccination involving Thailand and Vietnam (Huynh et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, only 4 (4.8%) of these intraregional papers can be categorised as purely South–South collaborations, with no involvement of co‐authors from UN agencies or research organisations associated with high‐income countries. This small subset of papers includes two papers focused on disease epidemiology in Indonesia including authors from Thailand and Indonesia (Eyanoer et al, 2011; Lestari et al, 2019), one paper on disease epidemiology in Myanmar involving authors from Myanmar and Thailand (Mon et al, 2012), and one paper on the efficacy of animal vaccination involving Thailand and Vietnam (Huynh et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This was followed by Japan (10; 14.9%), France (9; 13.4%), the United Kingdom (7; 10.4%) and other countries or categories including charities and multilateral organisations. Only a handful of papers reported funding from countries in the region: five papers acknowledged financial support from the Thai Research Council and/or Thai universities (Huynh et al, 2019; Lestari et al, 2019; Mon et al, 2012; Monteerarat et al, 2010; Win et al, 2014) and one paper benefitted from a scholarship by the Indonesia Endowment Fund for Education (Indrawan et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic variation of AIV circulation in previous studies showed that the influenza viruses in Indonesia identified in 2003-2020 showed that the subtype H5N1 virus clade 2.1.3, clade 2.3.2, subtype H9N2 and reassortant influenza viruses and other influenza virus subtypes were circulating in the live poultry market and farm in Indonesia. In 2019, co-circulation of HPAI-H5N1 clade 2.3.2.1c and LPAI-H9N2 were identified in duck farms during an AI outbreak in Yogyakarta province, Indonesia [21,22]. Circulation of several viruses in the environment has the opportunity to cause co-infection and subsequently resulted in viral mutations (antigenic drift and antigenic shift), including reassortment events between the H5N1 virus and other influenza viruses including H3 subtype [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Jonas et al (13) conducted research mapping H9N2 infection cases and demonstrated that the virus had spread to Java, Sumatra, Kalimantan, Sulawesi, and Bali. Infections with these viruses led to the death of 1000 ducks in Bantul Regency, Yogyakarta, in 2016 (14). The disease also causes respiratory problems in poultry, resulting in a 50-78% decrease in egg production and up to 2.7% mortality in laying hens in the Sidrap District, South Sulawesi (15).…”
Section: Introductionmentioning
confidence: 99%